FEATURES OF THE COMBINATION OF RELIGIOUS AND SECULAR CULTURES IN THE CONTEXT OF UZBEK YOUTH - Abdullayev Azimzhan Ashurvoy Ugli (Next Scientists Conferences, 2023)
The article "Peculiarities of the combination of religious and secular culture in the context of Uzbek youth" explores the unique aspects of the interaction of religious and secular elements in the behavior and values of modern Uzbek youth. The authors conduct an analysis based on empirical data, revealing how the youth of urbanized societies combines traditional religious values with elements of modern secular culture. The article examines the factors influencing this process, such as education, media, and social change. The research aims not only to expand the understanding of the socio-cultural aspects of Uzbek youth, but also to provide a basis for more effective interaction between traditional and modern aspects of their cultural experience.